Nigerian youths and internet fraud: A way out - Bamijoko, Gladys Francis (Corpus Intellectual, 2024)
Internet fraud is a significant and escalating problem, particularly affecting Nigerian youth. This article delves into the driving factors behind its rise, and the ensuing ramifications, and proposes countermeasures. The surge of internet fraud among Nigerian youth is an escalating concern. A central driver of this trend is Nigeria's economic climate, characterized by high unemployment rates and limited job prospects, which incentivizes many young individuals to seek alternative income sources. The allure of the internet, offering anonymity, entices these individuals, enabling them to conceal their identities behind a screen. The implications of internet fraud are extensive, extending beyond financial losses. It corrodes trust, tarnishes Nigeria's reputation, and obstructs economic growth. To combat this issue, several strategies are recommended. Firstly, parents play an indispensable role in shaping their children's values and ethical orientation. Encouraging open communication and instilling ethical principles can deter youth from fraudulent activities. Ethical education forms another critical element in countering internet fraud. Integrating ethical lessons into the educational curriculum enables young people to differentiate right from wrong. Fostering contentment and companionship is equally vital. Cultivating satisfaction with one's life and building strong, positive relationships can diminish the allure of quick, ill-gotten gains. Financial literacy plays a pivotal role in guiding youth toward judicious financial decisions. Recognizing the repercussions of fraudulent actions can dissuade them. Furthermore, education itself is a potent tool for redirecting youth towards constructive and ethical paths. Access to quality education equips them with the skills required to secure legitimate employment. In conclusion, internet fraud looms as a pressing issue among Nigerian youth, with extensive repercussions. To combat it effectively, a multifaceted approach is imperative, involving parents, educational institutions, and society at large. By addressing root causes and nurturing ethical values, Nigerian youth can be steered towards more constructive and ethical paths, thereby diminishing the prevalence of internet fraud.